Action mechanism of hypoglycemic principle 9-(R)-HODE isolated from cortex lycii based on a metabolomics approach - Yueqiu Liu; Yueqiu Liu; Xinyi Hu; Wen Zheng; Lu Zhang; Luolan Gui; Ge Liang; Yong Zhang; Liqiang Hu; Xin Li; Yi Zhong; Tao Su; et al. (Frontiers Media S.A., 2022)
The 9-(R)-HODE is an active compound isolated from cortex lycii that showed significant hypoglycemic effects in our previous in vitro study. In this study, 9-(R)-HODE's in vivo hypoglycemic activity and effect on alleviating diabetic complications, together with its molecular mechanism, was investigated using a metabolomics approach. The monitored regulation on dynamic fasting blood glucose, postprandial glucose, body weight, biochemical parameters and histopathological analysis confirmed the hypoglycemic activity and attenuation effect, i.e., renal lesions, of 9-(R)-HODE. Subsequent metabolomic studies indicated that 9-(R)-HODE induced metabolomic alterations primarily by affecting the levels of amino acids, organic acids, alcohols and amines related to amino acid metabolism, glucose metabolism and energy metabolism. By mediating the related metabolism or single molecules related to insulin resistance, e.g., kynurenine, myo-inositol and the branched chain amino acids leucine, isoleucine and valine, 9-(R)-HODE achieved its therapeutic effect. Moreover, the mediation of kynurenine displayed a systematic effect on the liver, kidney, muscle, plasma and faeces. Lipidomic studies revealed that 9-(R)-HODE could reverse the lipid metabolism disorder in diabetic mice mainly by regulating phosphatidylinositols, lysophosphatidylcholines, lysophosphatidylcholines, phosphatidylserine, phosphatidylglycerols, lysophosphatidylglycerols and triglycerides in both tissues and plasma. Treatment with 9-(R)-HODE significantly modified the structure and composition of the gut microbiota. The SCFA-producing bacteria, including Rikenellaceae and Lactobacillaceae at the family level and Ruminiclostridium 6, Ruminococcaceae UCG 014, Mucispirillum, Lactobacillus, Alistipes and Roseburia at the genus level, were increased by 9-(R)-HODE treatment. These results were consistent with the increased SCFA levels in both the colon content and plasma of diabetic mice treated with 9-(R)-HODE. The tissue DESI‒MSI analysis strongly confirmed the validity of the metabolomics approach in illustrating the hypoglycemic and diabetic complications-alleviation effect of 9-(R)-HODE. The significant upregulation of liver glycogen in diabetic mice by 9-(R)-HODE treatment validated the interpretation of the metabolic pathways related to glycogen synthesis in the integrated pathway network. Altogether, 9-(R)-HODE has the potential to be further developed as a promising candidate for the treatment of diabetes.